EVALUATING THE EFFECTIVENESS OF DIGITAL TRANSFORMATION IN ENTERPRISE BUSINESS MODELS (Collection of research papers «ECONOMIC STRATEGY AND PROSPECTS OF TRADE AND SERVICES SECTOR DEVELOPMENT», 2026)
The study is devoted to a comprehensive analysis of the economic efficiency of digital technologies implementation in the enterprise business model in the context of intensifying digital transformation of the economy. The relevance of the study is determined by the dichotomy between the growing volumes of investments in digital technologies and the absence of unified methodological approaches to assessing their economic efficiency, which complicates investment decision-making processes at enterprises.The theoretical and conceptual framework of the study is based on the integration of business model transformation theory, resource-based view of the firm, diffusion of innovations theory, and the concept of dynamic capabilities. This interdisciplinary approach allows considering the economic efficiency of digital technologies implementation as a multidimensional phenomenon encompassing the transformation of value proposition, reconfiguration of the resource base, and modification of organizational routines of the enterprise.The author proposes an integral indicator of economic efficiency of digital transformation of the business model, which includes: the coefficient of operational cost reduction, labor productivity index, customer base expansion coefficient, innovative diversification index, and digital maturity coefficient of business processes. The methodological architecture of the study is based on the application of complementary analytical tools for comprehensive assessment of digital transformation effectiveness.Based on the analysis of scientific literature and existing business practices, key determinants of economic efficiency of digital transformation are identified, including the level of digital competence of personnel, quality of change management, degree of integration of digital solutions, and alignment of digital strategy with overall business strategy. A four-stage structural-logical model of digital technologies implementation in the enterprise business model has been developed, which ensures a systematic phased approach to digitalization.The developed methodological approach to assessing the economic efficiency of digital technologies implementation in the enterprise business model has significant practical implications. The proposed toolkit enables justified selection of digital technologies for implementation, multi-dimensional analysis of alternative digital investments, optimization of the sequence of digital solutions implementation, identification and minimization of risks associated with digital transformation, and development of a balanced system of key performance indicators. The study formulated conceptual conclusions regarding the economic efficiency of digital technologies implementation in the enterprise business model and identified promising directions for further research in the field of digital transformation economics.
Keywords: digital transformation; business model; economic efficiency; digital technologies; digital maturity; competitiveness